2018
DOI: 10.1039/c7tc04696k
|View full text |Cite
|
Sign up to set email alerts
|

In situ electrochromic efficiency of a nickel oxide thin film: origin of electrochemical process and electrochromic degradation

Abstract: Schematically deciphering the electrochemical mechanism of the electrochromic NiOx thin film based on the Li+-ion electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 48 publications
0
56
0
Order By: Relevance
“…The implanted ions are limited by the charge layer in the crystal lattice. Therefore, accumulating with the increasing of the number of cy cles, the reversibility of the cycle deteriorates leading to the elec trochromic performance declining [4,20,32,42]. Fig.…”
Section: Tablementioning
confidence: 99%
“…The implanted ions are limited by the charge layer in the crystal lattice. Therefore, accumulating with the increasing of the number of cy cles, the reversibility of the cycle deteriorates leading to the elec trochromic performance declining [4,20,32,42]. Fig.…”
Section: Tablementioning
confidence: 99%
“…The XRD pattern revealed that NiO films deposited at DC powers of 100 and 150 W exhibit the polycrystallinity with a standard face-centered cubic structure which matching well with the JCPDS card No. 47-1049 of NiO [7]. The polycrystalline films show a well-defined peaks at 2 = 37.04 ∘ , 43.28 ∘ , 62.81 ∘ , and 75.47 ∘ which corresponded to the reflection of (111), (200), (220), and (311) planes, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Nickel oxide shows a great promise as an active electrochromic material due to the high coloration efficiency (CE), good cyclic reversibility, and low cost [4,5]. Thin film of NiO is widely used as the counter electrode layers in EC devices [4,6,7]. Various techniques have been used to deposit NiO thin films [6,8,9], but the sputtering technique is the most widely investigated, because the large-scale deposition sets are available, and high-quality films are obtained [4,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the replacement of oxygen with Fions at the oxygen sites, XPS analysis was performed ( Figure 3 and Figure S1). In the O1s spectra, the characteristic peaks at 528-530 and 531-533 eV correspond to bonds between the transition metal (M) and oxygen and oxygen vacancies, respectively (Figure 3a (Table S2) [32][33][34][35]. Furthermore, the Ni2p spectrum of NCMF consisted of characteristic peaks at 854-856 and 858-859 eV, which corresponded to Ni−O and M−F bonds, respectively ( Figure 3b).…”
Section: Resultsmentioning
confidence: 99%